Ethiopia Alive & Thrive Process Evaluation Survey 2013: Households - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
This dataset is the result of the household survey that was conducted to gather data for the process evaluation part of the impact evaluation of the Alive & Thrive (A&T) interventions in Ethiopia. The broad objective of the impact evaluation in Ethiopia is to measure the impact of A&T’s community-based interventions (CBI), delivered through the government's health extension program (HEP) platform, in the reduction of stunting and improvement of infant and young child feeding (IYCF) practices in two regions where the integrated family health program (IFHP) operates, namely Tigray and SNNPR (Southern Nations, Nationalities, and People’s Region). A&T is a six-year initiative funded by the Bill & Melinda Gates Foundation to facilitate change for improved infant and young child feeding (IYCF) practices at scale in Bangladesh, Ethiopia, and Viet Nam. The goal of A&T is to reduce avoidable death and disability due to suboptimal IYCF in the developing world by increasing exclusive breastfeeding (EBF) until 6 months of age and reducing stunting of children 0-24 months of age. The process evaluation (PE) is intended to answer one of the major learning objectives for the overall initiative, i.e., how A&T interventions achieve their impact. In Ethiopia, the studies that have been conducted as part of the process evaluation include: 1) a case study in 2011 to explore the extent of the training rollout among frontline health workers (FHWs) and to assess FHW and household exposure to interpersonal communication (IPC) tools developed by A&T, 2) a qualitative study in 2012 that included in-depth interviews with health extension workers (HEWs), HEW supervisors, and volunteers and shorter interviews with mothers and fathers to understand modalities of service delivery under IFHP and other A&T platforms, and 3) a quantitative survey in 2013 among FHWs and households to assess different aspects of service delivery and exposure to A&T community based program interventions. The Ethiopia process evaluation surveys of frontline health workers and households had two broad objectives. The first objective was to assess and understand the FHW work environment related to IYCF service delivery, in order to better answer how A&T interventions achieve impact. The second objective was to assess households’ exposure to the A&T program components/activities, as well as to compare IYCF knowledge and practices to the baseline survey in 2010 in order to get an idea of progress toward impact. The Ethiopia process evaluation survey used four separate questionnaires that aimed to capture elements along the program impact pathways. These tools include 1) a household questionnaire, 2) a staff questionnaire of HEWs, 3) a staff questionnaire of supervisors of HEWs, and 4) a volunteer community health promoters (VCHP) questionnaire. The main objectives of the Ethiopia household survey are to assess: 1) Exposure of the mothers/caregivers of children less than two years of age to key IYCF messages promoted by A&T, 2) Source of messages (FHW, mass media, community), 3) Sources of support for IYCF related issues, 4) Frequency of contacts with FHWs, 5) Knowledge and understanding of key IYCF messages promoted by A&T, and 6) Adoption of selected IYCF practices promoted by A&T and factors that facilitate the message.